Growth performance, testicular and epididymal characteristics of rabbit bucks fed black seed (Nigella sativa) supplemented diets - Hammed, O.O; Amao, O.A. (Nigerian Journal of Animal Science, 2023)
This study investigated supplementation effect of unprocessed black seed on the growth, testicular and epididymis characteristics of rabbit bucks. Forty (40) weaned male rabbits were weight-balanced and assigned to four dietary treatments with 10 animals each. The rabbits were fed with diet containing 16% crude protein and 2300 Kcal/kg metabolizable energy. The four experimental treatments were supplemented with black seed at levels of 0, 0.5, 1.0 and 1.5% denoted as T1, T2, T3 and T4, respectively. Data were obtained for weight gain and feed intake. Feed conversion ratio (FCR) was calculated accordingly. Other parameters evaluated include testicular and epididymal characteristics. Data collected were subjected to one-way analysis of variance. A significant (p<0.05) increase was observed in the growth indices as black seed supplementation increased up to 1.0%. Rabbits fed T3 recorded significantly (P<0.05) higher average daily gain, average daily feed intake and the best FCR. Significant (p<0.05) increase was observed in all the testicular and epididymal variables as black seed supplementation increased up to 1.0%. In conclusion, supplementation of black seed improved the growth performance, testicular and epididymal characteristics of rabbit bucks. Rabbits fed 1.0% black seed supplementation elicited the best performance in terms of the growth, testicular and epididymal characteristics.